2017
DOI: 10.1093/humrep/dex294
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of Type 2 diabetes is not increased in normal-weight women with PCOS

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
52
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 34 publications
5
52
1
2
Order By: Relevance
“…On the other hand, authors of several longitudinal studies demonstrate that the risk of T2DM in women with PCOS is linked mainly to overweight, to obesity, or to weight gain through the life 66,74,92,101,103. Similar results were achieved by Pelanis et al, who in a Nordic cross-sectional study found that no normal-weight woman with PCOS had been diagnosed with T2DM 125. On the basis of these observations, it can be suggested that routine OGTT may not be indicated in normal-weight women with PCOS.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…On the other hand, authors of several longitudinal studies demonstrate that the risk of T2DM in women with PCOS is linked mainly to overweight, to obesity, or to weight gain through the life 66,74,92,101,103. Similar results were achieved by Pelanis et al, who in a Nordic cross-sectional study found that no normal-weight woman with PCOS had been diagnosed with T2DM 125. On the basis of these observations, it can be suggested that routine OGTT may not be indicated in normal-weight women with PCOS.…”
supporting
confidence: 61%
“…On the basis of these observations, it can be suggested that routine OGTT may not be indicated in normal-weight women with PCOS. The recommendations of OGTT in women with diagnosed PCOS vary between different guidelines, in frequency of testing and selection of the people included to the screening, depending on their age, BMI, previous gestational diabetes mellitus, or family history of T2DM, that was comprehensively described by Pelanis et al125 Some authors convince that not all patients with PCOS should be screened for T2DM and that OGTT could be performed only in high-risk patients, that was already submitted by Glintborg and Andersen 126. Authors of the actual analysis support the opinion postulated by Torchen in a recently published review,111 that screening for T2DM is needed in all patients with PCOS, as there are longitudinal observations that even normal-weight PCOS women are at increased risk of abnormal glucose metabolism.…”
mentioning
confidence: 99%
“…Although numerous studies have found that testosterone is closely associated with insulin resistance and could further lead to diabetes, no obvious correlations were found between testosterone and FPG, 2hPG or HbA1c in the present study, which was consistent with a Nordic multicentre cross‐sectional study . However, the effects of other confounding factors could not be excluded, such as physical activity, smoking, alcohol consumption and family history of diabetes, which may cause differences in the results of association studies.…”
Section: Discussionsupporting
confidence: 70%
“…Although numerous studies have found that testosterone is closely associated with insulin resistance and could further lead to diabetes, no obvious correlations were found between testosterone and FPG, 2hPG or HbA1c in the present study, which was consistent with a Nordic multicentre cross-sectional study. 30 However, it should be noted that the measurement of low serum aldosterone concentrations by LC-MS/MS remains a challenge, despite being a relatively more accurate and reliable method when compared with immunoassays. [32][33][34] Although no clear causality between steroid hormones and abnormal glucose metabolism was proven in our study, increasing evidences indicate that abnormal patterns of steroid hormones, such as hyperandrogenaemia and hyperaldosteronaemia in women with PCOS, contribute to hyperglycaemia and may increase the risk of prediabetes and T2DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation